Effects of altered thyroid states on oxidative stress parameters in rats - OKTAY, NİHAL ŞEHKAR (Walter de Gruyter GmbH, 2017)
Thyroid hormones are effective on oxidant-antioxidant balance by leading basal metabolic rate. In this study, the effects of altered thyroid states on low density lipoprotein (LDL) oxidation and oxidative stress parameters were investigated in an experimental animal model. Thirty female Wistar Albino rats were equally divided into 3 groups as follows: control group; hypothyroid group (methimazole (75 mg/100 g was added to diet); hyperthyroid group [L-thyroxine (0.4 mg/100 g was added to diet)]. Oxidized LDL (ox-LDL) levels, thyroid, and lipid parameters were determined in serum. Also lipid peroxidation (LPO), sialic acid (SA) and glutathione levels (GSH), as well as superoxide dismutase (SOD) and catalase (CAT) activities were determined in tissue samples. A significant increase in lipid parameters was observed in hypothyroid group, whereas these parameters were decreased in hyperthyroid group compared to control group. For ox-LDL levels, a significant increase was observed both in hypothyroid and hyperthyroid groups. In brain, liver and kidney tissues, LPO and SA levels were increased, whereas GSH levels were decreased both in hypothyroid and hyperthyroid groups. The SOD and CAT activities were significantly decreased in hypothyroid group, however, they were increased in hyperthyroid group compared to control group. Both hypothyroid and hyperthyroid conditions modify the oxidant-antioxidant state in serum and tissues. Increased SOD and CAT activities in hyperthyroid group suggest that elevated thyroid hormones can reduce oxidative stress by maintaining antioxidant defense and they might have a protective effect on some tissues against oxidants. © 2017 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: antioxidant-oxidant parameters; hyperthyroid; hypothyroid; oxidized LDL